Decoding the IT value problem, + website : an executive guide for achieving optimal ROI on critical IT investments - Fell, Gregory J., 1964- (Hoboken, New Jersey : Wiley, 2013)
"Gain greater returns from your IT investmentsRevealing the secrets to proven, effective strategies that enable businesses to leverage the full value of highly expensive IT investments, Decoding the IT Value Problem is a no-nonsense guide for making smart IT investments and cutting through the noise of vendor marketing and media hype. Author Gregory Fell describes in rich detail the actual processes, frameworks, infrastructure and discipline required to develop and execute corporate IT strategies that areprofitable and sustainable. Provides a proven framework for developing and successfully executing profitable IT strategies Plain English guidance for gaining the most return on investment from critical IT investments Explores developing and executing IT strategy; forecasting, calculating and managing IT costs; leveraging IT investments to drive business growth; IT and the evolving global economy; IT value management; communicating IT value across the enterprise; and leading change, transformation and innovation If you're a senior level manager or executive responsible for managing IT value in your business, Decoding the IT Value Problem is the practical and clearly written guide you'll turn to, with tools and tips for smart investment and management of IT costs"--
Moore's Law and the Cost of ITAnd the Moral of the Story Is . . .; Some IT Projects Are Very Expensive; Chapter 12 The CFO's Perspective; Cash, Risk, and Benefits; Chapter 13 Optimizing the CEO-CIO Relationship; Making a Strategic Contribution; The CIO Evolution; Chapter 14 Conclusions; Don't Burn Your Money; Note; Recommended Reading; About the Author; Index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
John Wiley and Sons
Keywords: Information technology; Information technology -- Cost effectiveness; Capital investments -- Evaluation; Electronic data processing; Technologie de l'information.; Technologie de l'information; Investissements de capitaux; information technology; BUSINESS & ECONOMICS -- Strategic Planning; Electronic data processing; Capital investments -- Evaluation; Information technology; Information technology -- Cost effectiveness